Improving Students’ Reading Comprehension Through Interactive Read Aloud Method at SMP Negeri 4 Dumoga - Maringka, Putri F.; Mogea, Tini; Hampp, Paula (English Education Department, 2025)
This research focuses on the challenges faced by 8th grade students at SMP Negeri 4 Dumoga, with an emphasis on their difficulties in English comprehension. The researcher found that many students find it difficult to read and understand English texts. Based on this problem, the Interactive Read Aloud method is a way that can be used to improve students' reading comprehension. This research used a pre-experimental design that included a one-group pre-test and post-test. The research was conducted at SMP Negeri 4 Dumoga and the research subjects were twenty students of 8th grade. In the data collection process, the researcher used a test consisting of twenty questions in the form of multiple choice. Based on the results obtained from the analyzed data, students' reading comprehension increased as evidenced by the mean score of the pre-test (39.25) and the mean score of the post-test (74.50), where there was an increase in scores from pre-test to post-test. Before the treatment, the students' scores were lower than the scores after the treatment. This shows that the use of interactive read aloud method is effective in improving reading comprehension. Since this method has the ability to adjust to students' different ability levels, it is recommended that junior high school teachers use the interactive read aloud method to improve students' reading comprehension